Otologic cause of giddiness in a tertiary hospital: Our experience - Soumick Ranjan Sahoo (Indian Journal of Health Sciences and Biomedical Research KLEU, 2020)
Context: Giddiness affects a large percentage of population at any time. It also forms a large part of patient group attended by neurologists, cardiologists, and also commonly referred to otolaryngology clinics. Among otologic causes, those commonly regarded are benign paroxysmal positional vertigo (BPPV), Ménière's disease, Labyrinthitis, and Vestibular neuronitis. Aim: The aim is to study the proportion of patients of vertigo referred to ear, nose, and throat (ENT) Outpatient Department (OPD), having otologic cause of vertigo and to study common causes of otologic cause of vertigo. Settings and Design: Prospective observational study. Subjects and Methods: A data was recorded for 125 subjects above the age of 15 years, complaining for vertigo, presenting to ENT OPD of a tertiary care center from January 2019 to January 2020. A thorough detailed history was taken from all patients. Otology and oto-neurological examination was thoroughly done. Computed tomography scan/magnetic resonance imaging kept reserved only for those patients in whom there is a suspicion of cerebellopontine angle tumor or stroke. Based on these batteries of tests a diagnosis of otologic cause of vertigo was made. All the findings were recorded into a Data sheet. Results: The result it was found that 28.8% of the patients (total 36) who complained of vertigo had an otologic cause for it. From the tests conducted, BPPV occurred as the most common cause (23.2%). Others were vestibular neuronitis (3.2%) and labyrinthine causes (1.6%) Meniere's disease (0.8%). The maximum affected age group was from 41 to 60 years and frequency of females was reported to be higher than males. Conclusion: The result of this study draws our attention to the causes of vertigo that are from otologic disease. This information can also be used for awareness amongst physicians and the general practitioners around this hospital for referring vertigo cases to ENT OPD.